2023
DOI: 10.3389/fneur.2023.1100736
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic system impairment in nonathlete older male adults who played contact sports in their youth associated with cognitive decline: A diffusion tensor image analysis along the perivascular space study

Abstract: Background and purposeExposure to contact sports in youth causes brain health problems later in life. For instance, the repetitive head impacts in contact sports might contribute to glymphatic clearance impairment and cognitive decline. This study aimed to assess the effect of contact sports participation in youth on glymphatic function in old age and the relationship between glymphatic function and cognitive status using the analysis along the perivascular space (ALPS) index.Materials and methodsA total of 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…There is also a paper that examines the ALPS-index calculated for the right hemisphere and the ALPS-index calculated for the left hemisphere separately. 16 , 19 , 69 , 165 , 166…”
Section: Consideration For the Methodology Of Dti-alpsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a paper that examines the ALPS-index calculated for the right hemisphere and the ALPS-index calculated for the left hemisphere separately. 16 , 19 , 69 , 165 , 166…”
Section: Consideration For the Methodology Of Dti-alpsmentioning
confidence: 99%
“…There is also a paper that examines the ALPS-index calculated for the right hemisphere and the ALPS-index calculated for the left hemisphere separately. 16,19,69,165,166 Some studies employ atlas based placement. 56,147 Yokota et al coregistered diffusion maps to the DTI-81 atlas of the International Consortium for Brain Mapping (ICBM) and established ROIs for projection and association fiber regions.…”
Section: Placement Of Roimentioning
confidence: 99%
“…behavior disorder, 27 obstructive sleep apnea, 28 and metabolic syndrome, 29 and in participants playing contact sports 30 and patients with AD and PD. Furthermore, some lifestyle activities, including sleep, 31,32 could have significant associations with the glymphatic system.…”
Section: Clinical Significancementioning
confidence: 99%
“…Moreover, it has been reported that impairments in the waste clearance system are related to CSF absorption and ISF bulk‐flow (i.e., glymphatic system; Fig. 1) in patients with idiopathic intracranial hypertension, 26 isolated rapid eye movement (REM) sleep behavior disorder, 27 obstructive sleep apnea, 28 and metabolic syndrome, 29 and in participants playing contact sports 30 and patients with AD and PD. Furthermore, some lifestyle activities, including sleep, 31,32 could have significant associations with the glymphatic system.…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation